2009
DOI: 10.1111/j.1365-2516.2009.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo stability of diluted recombinant factor VIII for continuous infusion use in haemophilia A

Abstract: Factor VIII (FVIII) replacement by continuous infusion (CI) is used postoperatively or after significant bleeding. For young paediatric patients, CI may require FVIII dilution. Variable stabilities of diluted full-length recombinant FVIII Kogenate FS (KG-FS) have been reported under different storage conditions. We investigated the recovery and stability of diluted KG-FS in vitro and in vivo. Kogenate FS was diluted to 50-120 U mL(-1) and its recovery and stability in glass vials or polypropylene syringes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…Concentrated FVIII solutions retain excellent stability at room temperature over prolonged time periods [4,7,22,23,37] in contrast to the reduced stability of diluted FVIII solutions [36,38,39]. Limited adsorption of FVIII to the walls of some infusion sets material (polypropylene syringes and polyethylene tubing) is suggested to cause initial decrease of activity in diluted solutions [38,39]. This, however, did not appear to affect haemostatic efficacy nor clinical outcome in patients treated with CI [23,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrated FVIII solutions retain excellent stability at room temperature over prolonged time periods [4,7,22,23,37] in contrast to the reduced stability of diluted FVIII solutions [36,38,39]. Limited adsorption of FVIII to the walls of some infusion sets material (polypropylene syringes and polyethylene tubing) is suggested to cause initial decrease of activity in diluted solutions [38,39]. This, however, did not appear to affect haemostatic efficacy nor clinical outcome in patients treated with CI [23,39].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, 59% and 79% centres in USA and Canada, respectively, dilute reconstituted concentrates in normal saline [29,36]. Concentrated FVIII solutions retain excellent stability at room temperature over prolonged time periods [4,7,22,23,37] in contrast to the reduced stability of diluted FVIII solutions [36,38,39]. Limited adsorption of FVIII to the walls of some infusion sets material (polypropylene syringes and polyethylene tubing) is suggested to cause initial decrease of activity in diluted solutions [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Revel-Vilk et al [22] demonstrated that these in-vitro losses of FVIII did not diminish the efficacy of CI in vivo. CI of rFVIII-FS diluted to 80 U/mL with 0.9% saline administered with a syringe pump to a boy with severe hemophilia postsurgically resulted in stable FVIII activity levels within the target range [22]. Nevertheless, before initiating CI it is advisable to test the stability of each concentrate type and to assay its compatibility with the particular infusion set to be used for CI.…”
Section: Historical Background and Rationale For Continuous Infusionmentioning
confidence: 99%
“…However, in contrast to an excellent stability of undiluted rFVIII-FS for more than 7 days (Figure 29.2) [16], the dilution further than by the regular reconstitution resulted in initial loss of activity and decreased stability of product stored in the vials or syringes (Figure 29.3) [21,22]. Revel-Vilk et al [22] demonstrated that these in-vitro losses of FVIII did not diminish the efficacy of CI in vivo. CI of rFVIII-FS diluted to 80 U/mL with 0.9% saline administered with a syringe pump to a boy with severe hemophilia postsurgically resulted in stable FVIII activity levels within the target range [22].…”
Section: Historical Background and Rationale For Continuous Infusionmentioning
confidence: 99%
“…Infuzijsko hitrost lahko nato hitrost infuzije (ie/kg/uro) očistek (ml/kg/uro) = izmerjena aktivnost faktorja (ie/ml) določimo z vsakodnevnim računanjem očistka ali pa po obrazcu neposredno izračunamo hitrost v ml/uro. Izbrani koagulacijski faktor se pripravi po priloženih navodilih proizvajalca brez dodatnega redčenja (pri zelo majhni količini topila v viali se redči s fiziološko raztopino) (63). Za prepreči-tev tromboflebitisa na perifernih venah se koagulacijskemu faktorju doda 4 E/ ml heparina.…”
Section: Kontinuirana Infuzija Fviii / IXunclassified